Analisa Rasio Keuangan Daerah untuk Mengukur Kinerja Pendapatan, Pajak, dan Belanja Kabupaten Blitar Tahun 2019-2023 - Mega Tunjung Hapsari; Eva Debi Fitriani; Ira Sri Agmiana; Arina Eka Nur Fadhilah; Rihhadatul Aisy Qatrunnada S; Chasa Puput Tri Mei A; Saraya Izzati Shabira (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Regional financial ratio analysis is important to see how the region can manage finances effectively and efficiently. The results of financial analysis in Blitar Regency for the years 2019-2023 show that the Regional Financial Dependency Ratio fluctuates, with a high average of 72%, indicating a significant dependence on the central government. The Regional Financial Freedom Ratio, although increased during the Covid-19 pandemic, remains low at an average of 24%, indicating a pattern of consultative relations with the central government. The Decentralization Degree Ratio is also low, averaging 12.99%, indicating a lack of regional capacity to generate their own income. The Tax Effectiveness Ratio shows a very effective performance with an average of 113%, indicating the realization of tax revenue exceeding the target. The ratio of Direct and Indirect Expenses shows less efficiency, with indirect expenses being more dominant. Overall, although the effectiveness of tax and capital expenditure shows positive results, financial dependence and the level of decentralization still require attention to improve the financial independence and efficiency of the Blitar Regency area.